2018
DOI: 10.4236/as.2018.92013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Live Food on the Coloration and Growth in Guppy Fish, <i>Poecilia reticulata</i>

Abstract: Colour production in fish is due mostly to food. In conditions of captivity, the type of food is restricted, while various types of food are used in aquaculture, from processed dry food to small aquatic animals. In this study, we used nauplii of Artemia franciscana, "water fleas" Moina wierzejski, micro-worm Panagrellus redivivus, and commercial flakes. We used Poecilia reticulata, which is one of the most traded fish in ornamental aquaculture and hypothesise that if the live food influences the coloration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…ISSN online 2007-9621 Trejo-Albarrán, R., Gómez-Márquez, J. L., Granados Ramírez, J. G., Trujillo Jiménez, P., Castro Franco, R., Bustos Zagal, G., & Granjeno Colín, A. E. Cladóceros presentes en ecosistemas acuáticos de Morelos, México, con posibilidad de uso como alimento vivo | 1-18 Arce et al (2018), Ferrão-Filho et al (2003 De igual forma, se recomienda evaluar otros procesos de enriquecimiento y fuentes de ácidos grasos con el objetivo de lograr aumentar la tasa de crecimiento durante esta fase y consolidar el proceso de larvicultura. Atencio et al (2014) señalan que la mayor mortalidad larval en peces se presenta entre el segundo y cuarto día de inicio de la alimentación exógena.…”
Section: Discussionunclassified
“…ISSN online 2007-9621 Trejo-Albarrán, R., Gómez-Márquez, J. L., Granados Ramírez, J. G., Trujillo Jiménez, P., Castro Franco, R., Bustos Zagal, G., & Granjeno Colín, A. E. Cladóceros presentes en ecosistemas acuáticos de Morelos, México, con posibilidad de uso como alimento vivo | 1-18 Arce et al (2018), Ferrão-Filho et al (2003 De igual forma, se recomienda evaluar otros procesos de enriquecimiento y fuentes de ácidos grasos con el objetivo de lograr aumentar la tasa de crecimiento durante esta fase y consolidar el proceso de larvicultura. Atencio et al (2014) señalan que la mayor mortalidad larval en peces se presenta entre el segundo y cuarto día de inicio de la alimentación exógena.…”
Section: Discussionunclassified
“…Penampilan warna pada ikan dipengaruhi oleh faktor genetik, lingkungan dan interaksi antara faktor genetik dan lingkungan (Uribe et al, 2018). Pola warna dikontrol oleh gen dan diturunkan dari induk kepada keturunannya (Laimeheriwa et al, 2019).…”
Section: Pendahuluanunclassified
“…In comparison, the majority of scientifically verified reports about aquarium fish nutrition also concern the application of natural food for larval stages [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], but there are mostly vague reports about diets for fish which already underwent larval metamorphosis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. More attention has thus far been paid only to the Siamese fighting fish, Betta splendens [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], commonly known as the “betta”.…”
Section: Introductionmentioning
confidence: 99%
“…as a supplementary ingredient in formulated pellets for poecilid livebearers [ 32 , 33 ]. In addition, a highly diversified mixture of natural and artificial food proved to be the most preferable for the green swordtail, Xiphophorus hellerii [ 27 ], while different live feed were shown to be an upgrade from commercial flakes when fed to the guppy, Poecilia reticulata [ 35 ]. Finally, nutritional studies on the model species, the zebrafish Danio rerio (Danionidae), have shown that intensive rearing with only Artemia sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation